Legal Policy Of Sustainable Tourism Development: Toward Community-Based Tourism In Indonesia - I Nyoman NURJAYA (PT Keberlanjutan Strategis Indonesia, 2023)
Tourism development is one leading and potential element of the national establishment that can be generated to realize the ideology of controlling and utilizing natural resources and cultural diversity of the State to increase the national economic growth. In facing the changes in global economic, social structure, and living environment, the national and international tourism development trend to become a global phenomenon and economic practices for obtaining income and revenue of the respective country. In this respect, the rights to tourism particularly the rights of the local community within the area of tourism destinations, have not attracted much attention in the academic world. Little attention, regulation and policy that enacted for such a legal issue in the country of Indonesia. It may be because this tourism right is intentionally not considered a fundamental right as well as other human beings and ecological rights. However, these rights are essential in establishing sustainable tourism in the country as a part of human rights in tourism development. The article attempts to outline the conceptual dimension of sustainable tourism development. It provides an overview international policy framework, as well as the existence of national legal instruments for which the tourism industry in the country can be employed to enhance the State's income and revenue for the most significant welfare and prosperity of the people as mandated by the 1945 Constitution.